FEATURES OF DEFEAT OF THE THYMUS AND CRITERIA OF BEFORE AND AFTER OPERATING PROGNOSIS OF THYMECTOMY IN WOMEN WITH GENERALIZED MYASTHENIA - Remniova, N.A.; Protsenko, E.S. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
First studied features of defeat of the thymus in women with generalized myasthenia flowing on a background atrophy and hyperplasia of thymus with further development of criteria of before and after the operating prognosis of thymectomy. It is set that GM in women flows on a background atrophy of thymus with making progress thymycal (suppressor) insufficiency or on a background hyperplasia with thymycal hyperactivity and these morphological displays GM in a thymus have different pathogenesis. By the criteria of ineffectiveness of thymectomy at GM it is necessary to count atrophy of thymus, absolute deficit of T-suppressor-cell in the parenchyma of thymus and whey of blood, deficit of IgG and IgA, in the whey of blood.